After the Nicaraguan Non‐Payment Crisis: Alternatives to Microfinance Narcissism. Issue 4 (1st July 2013) - Bastiaensen, Johan; Marchetti, Peter; Mendoza, René; Pérez, Francisco
ABSTRACT This article argues against 'microfinance narcissism' and calls for a re‐politicization of the microfinance paradigm. The dominant verdict on microcredit has undergone a damning transformation, from 'magic bullet for poverty reduction' to 'cause of suicide'. Nowadays, both radical critics and mainstream voices deplore microcredit's negative impact on micro‐entrepreneurs. They argue for a reorientation where credit is targeted at established small and medium‐sized enterprises, particularly in rural areas. The crisis in microfinance worldwide, including burgeoning protests, are viewed as proof of the commercial derailment and/or misplaced faith in microfinance's positive social and economic impact on the poor. This article engages with this debate through a study of the Nicaraguan micro‐finance crisis. It challenges existing analyses that pin the crisis on agricultural over‐indebtedness, lack of due diligence, or Sandinista populist politics. Illustrating the dangers of neglecting the diverse nature of microfinance, it reveals the paradoxical outcomes of the crisis: a refocus on the urban at the expense of agricultural credit for small and medium enterprises and a consolidation of the power of national processing elites. Nicaragua's Non‐Payment Movement is also shown to be both a product of elite manipulation and an expression of legitimate resistance to an industry that turns a blind eye to the manner in which markets and politics constrain clients' potential.